Mental health impact of the first wave of COVID-19 pandemic on Spanish healthcare workers: A large cross-sectional survey - Alonso, Jordi; Vilagut, Gemma; Mortier, Philippe; Ferrer, Montse; Alayo, Itxaso; Aragón-Peña, Andrés; Aragonès, Enric; Campos, Mireia; Cura-González, Isabel D.; Emparanza, José I.; Espuga, Meritxell; Forjaz, Maria João; et al. (Revista de psiquiatria y salud mental (English ed.), 2021)
Healthcare workers are vulnerable to adverse mental health impacts of the COVID-19 pandemic. We assessed prevalence of mental disorders and associated factors during the first wave of the pandemic among healthcare professionals in Spain. All workers in 18 healthcare institutions (6 AACC) in Spain were invited to web-based surveys assessing individual characteristics, COVID-19 infection status and exposure, and mental health status (May 5 – September 7, 2020). We report: probable current mental disorders (Major Depressive Disorder-MDD- [PHQ-8≥10], Generalized Anxiety Disorder-GAD- [GAD-7≥10], Panic attacks, Posttraumatic Stress Disorder –PTSD- [PCL-5≥7]; and Substance Use Disorder –SUD-[CAGE-AID≥2]. Severe disability assessed by the Sheehan Disability Scale was used to identify probable “disabling” current mental disorders. 9,138 healthcare workers participated. Prevalence of screen-positive disorder: 28.1% MDD; 22.5% GAD, 24.0% Panic; 22.2% PTSD; and 6.2% SUD. Overall 45.7% presented any current and 14.5% any disabling current mental disorder. Workers with pre-pandemic lifetime mental disorders had almost twice the prevalence than those without. Adjusting for all other variables, odds of any disabling mental disorder were: prior lifetime disorders (TUS: OR=5.74; 95%CI 2.53-13.03; Mood: OR=3.23; 95%CI:2.27-4.60; Anxiety: OR=3.03; 95%CI:2.53-3.62); age category 18-29 years (OR=1.36; 95%CI:1.02-1.82), caring “all of the time” for COVID-19 patients (OR=5.19; 95%CI: 3.61-7.46), female gender (OR=1.58; 95%CI: 1.27-1.96) and having being in quarantine or isolated (OR= 1.60; 95CI:1.31-1.95). One in seven Spanish healthcare workers screened positive for a disabling mental disorder during the first wave of the COVID-19 pandemic. Workers reporting pre-pandemic lifetime mental disorders, those frequently exposed to COVID-19 patients, infected or quarantined/isolated, female workers, and auxiliary nurses should be considered groups in need of mental health monitoring and support. Los profesionales sanitarios son vulnerables al impacto negativo en salud mental de la pandemia COVID-19. Evaluamos la prevalencia de trastornos mentales y factores asociados durante la primera oleada de la pandemia en sanitarios españoles. Se invitó a todos los trabajadores de 18 instituciones sanitarias españolas (6 CCAA) a encuestas en línea evaluando características individuales, estado de infección y exposición a COVID-19 y salud mental (5 Mayo – 7 Septiembre, 2020). Reportamos: probables trastornos mentales actuales (Trastorno depresivo mayor TDD [PHQ-8≥10], Trastorno de ansiedad generalizada TAG [GAD-7≥10], Ataques de pánico, Trastorno de estrés postraumático TEP [PCL-5≥7]; y Trastorno por uso de sustancias TUS [CAGE-AID≥2]. La interferencia funcional grave (Escala de Discapacidad de Sheehan) identificó los probables trastornos “discapacitantes”. Participaron 9.138 sanitarios. Prevalencia de cribado positivo: 28,1% TDD; 22,5% TAG, 24,0% Pánico; 22,2% PTE; y 6,2% TUS. En general, el 45,7% presentó algún trastorno mental actual y el 14,5% algún trastorno discapacitante. Los sanitarios con trastornos mentales previos tuvieron el doble de prevalencia que aquellos sin patología mental previa. Ajustando por todas las variables, el trastorno mental incapacitante se asoció positivamente con: trastornos previos (TUS: OR=5.74; 95%CI 2.53-13.03; Ánimo: OR=3.23; 95%CI:2.27-4.60; Ansiedad: OR=3,03; IC 95%: 2,53-3,62); edad 18-29 años (OR=1,36; IC 95%: 1,02-1,82); atender “siempre” a pacientes COVID-19 (OR=5,19; IC 95%: 3,61-7,46), género femenino (OR=1,58; IC 95%: 1,27-1,96) y haber estado en cuarentena o aislado (OR=1,60; IC 95%: 1,31-1,95). Uno de cada 7 sanitarios españoles presentaron un probable trastorno mental discapacitante durante la primera oleada de COVID-19. Aquéllos con trastornos mentales alguna vez antes de la pandemia, los que están expuestos con frecuencia a pacientes con COVID-19, los infectados o en cuarentena / aislados, las mujeres y las enfermeras auxiliares deben considerarse grupos que necesitan seguimiento y apoyo de su salud mental.